Generalized Substorm Current Wedge Model: Two Types of Dipolarizations in the Inner Magnetosphere. Issue 9 (16th September 2020) - Ohtani, S.; Motoba, T.; Takahashi, K.; Califf, S.
Abstract: The present study investigates dipolarization signatures in the inner magnetosphere using sharp geosynchronous dipolarizations as a reference. The results are summarized as follows: (1) The region of sharp and structured dipolarizations expands earthward while dipolarizations are sustained at geosynchronous orbit; (2) within 5 R E from Earth, dipolarization signatures are often smooth and gradual, resembling midlatitude positive bays, and they start simultaneously with substorm onsets; (3) off the equator (>0.5 R E ), sharp dipolarizations often take place before geosynchronous dipolarizations. These results can be explained by a model current system with R1‐sense and R2‐sense current wedges (R1CW and R2CW) if (a) the R1CW, which is located outside, is more intense than the R2CW in total current, (b) the R1CW stays outside of geosynchronous orbit, and (c) the R2CW moves earthward. The model suggests that the region of sharp dipolarizations is confined between the two current wedges, and it expands earthward as the R2CW moves earthward (Result 1). Sufficiently earthward of the R2CW, the remote effect of the R1CW dominates that of the R2CW, and accordingly, magnetic disturbances resemble midlatitude positive bays (Result 2). Since the timing of sharp dipolarizations is determined by the passage of the R2CW, they take place earlier for outer flux tubes. Away from the magnetic equator, sharp dipolarizations can precede geosynchronous dipolarizations especially if the magnetic configuration is stretched (Result 3). Thus, this double‐current wedge model explains the variability of dipolarization signatures at different distances, and it may be regarded as a generalized substorm current wedge model. Key Points: The region of sharp dipolarizations expands earthward in the inner magnetosphere while geosynchronous dipolarizations are sustained Dipolarizations at r < 5 Re are often smooth and gradual resembling midlatitude positive bays, and start simultaneously with substorm onsets In the inner magnetosphere, sharp dipolarizations start earlier off the equator, often before geosynchronous dipolarizations